English for Academic Purposes: the Cinderella of higher education socialisation structures - Leigh, Evelyn Sandra (2020)
In an increasingly internationalised higher education (HE) context, this thesis challenges the traditional concept of English for Academic Purposes (EAP) centres as merely language support units for international students. International students have increasingly become important stakeholders in higher education institutes (HEIs) especially those wishing to promote a global profile and increase international student recruitment. In response, many institutions now have EAP or English language units to support international students with language problems. Such an intervention, however, denies the complexity of transitioning into higher education for these students and trivialises the modern role of EAP. Moreover, partnerships between private providers of EAP programmes and universities pose a threat to in-house English language centres and risk deprofessionalising university EAP staff. This raises questions about the real value of today’s EAP centres, the purposes they serve and how best to remain organic in their support of international students. Current EAP research has neither sufficiently focused on the experiences of former EAP students nor considered its wider impact on their socialisation, which would highlight its changing purpose in a dynamic HE environment. To close this gap, this thesis investigates the socialisation experiences of 13 international students to understand their post-EAP experiences and how their EAP education affected their socialisation. Data were collected through interviews with students, subject lecturers, and EAP tutors and analysed using socialisation theories. A complex picture of students’ socialisation experiences emerges indicating that EAP tuition is more than just a linguistic intervention for these students. Despite some inconsistencies between students’ EAP education and academic degree experiences, the former was perceived as a valuable pedagogical intervention that eased students’ academic transitions. Undertaking an EAP course allowed students to anticipate university expectations, be familiar with assessment tasks and campus settings. The study also revealed the importance of physical and virtual spaces to students’ socialisation experiences. However, to remain effective, in-house EAP provision must adopt an iterative approach to evaluating practice and engage in ongoing dialogues with both subject lecturers and former students. Such dialogues need to be facilitated by an institutional top-down approach to students’ socialisation. Doing so would help reconceptualise such EAP centres as fundamental socialisation structures supporting international student retention and very possibly, institutional internationalisation strategies.